Quality assurance of isocentres for passive proton beam nozzles using motion capture cameras. (February 2020) - Cheon, Wonjoong; Jo, Kwanghyun; Ahn, Sung Hwan; Cho, Junsang; Han, Youngyih
Highlights: Developed a QA system which determines mechanical, radiation, and imaging isocentres in three-dimensions. The new system verifies the coincidence of isocentres in three-dimensions and visualized the coincidence. The new system is semi-automatic utilizing a visual tracking system. Abstract: Purpose: The objective of this work is to determine mechanical, radiation, and imaging isocentres in three-dimensional (3D) coordinates and verifying coincidence of isocentres of passively scattered proton beam using a visual tracking system (VTS) and an in-house developed phantom named the Eagle. Methods: The Eagle phantom consists of two modules: The first, named Eagle-head, is used for determining 3D mechanical isocentre of gantry rotation. The second, named Eagle-body, is used for determining 3D radiation and imaging isocentres. The Eagle-body has four slots wherein radiochromic films were inserted for measuring the 3D radiation isocentre and a metal bead was embedded in the centre of one cube to determine the imaging isocentre; this was determined by analysing cone-beam computed tomography images of the cube. Infrared reflective markers that can be tracked by VTS were attached to the Eagle at predetermined locations. The tracked data were converted into 3D treatment room coordinates. The developed method was compared with other methods to assess accuracy. Results: The isocentres were determined in mm with respect to the laser isocentre. The mechanical, radiation, and imaging isocentres were (−0.289, 0.189, 0.096), (−0.436, −0.217, 0.009), and (0.134, 0.142, 0.103), respectively. When compared with other methods, the difference in coordinates was (−0.033, −0.107, 0.014) and (0.003, 0.067, 0.039) for radiation and imaging isocentres, respectively. Conclusion: The developed system was found to be useful in providing fast and accurate measurements of the three isocentres in the 3D treatment room coordinate system.